2016
DOI: 10.5530/jyp.2016.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Ethical Authorship: A Comparative Study Between Medical And Pharmacy Faculty

Abstract: Aim:The study was aimed to assess the knowledge on understanding ethical authorship of research publications among the medical and pharmacy faculty members of India. Materials and Methods: We have selected 54 numbers of medical faculty members and 41 numbers of pharmacy faculty members from different parts of India to assess their understanding and knowledge on concept in authorship issues for ethical publication by questionnaire and telephone interview. Results: It showed a significant higher number of public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Gift authorship was prevalent in more than 80% of the medical faculty and 29% of the pharmacy faculty. 13 In another study that used a national survey to assess the medical student experience with authorship, the investigators found that two-thirds of the medical students never received formal training in authorship guidelines previously. 14 Moreover, close to 25% of the respondents indicated that the criteria for authorship were never clarified to them.…”
Section: Discussionmentioning
confidence: 99%
“…Gift authorship was prevalent in more than 80% of the medical faculty and 29% of the pharmacy faculty. 13 In another study that used a national survey to assess the medical student experience with authorship, the investigators found that two-thirds of the medical students never received formal training in authorship guidelines previously. 14 Moreover, close to 25% of the respondents indicated that the criteria for authorship were never clarified to them.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences are even visible for publishers within the same subject [5,24]. A majority of the authors of our selected studies referred to the authorship criteria published by ICMJE (see Table 1) [1,5,20,21,22,23,24,28,29]. The ICMJE criteria are accepted worldwide by the journals from medicine and related health sciences disciplines.…”
Section: Authorship Criteriamentioning
confidence: 99%
“…[1, 22,23,24,27,30] Gift authorship Granting authorship as favor to one who does not qualifies the authorship criteria. [1,5,22,23,24,28] Guest/Honorary authorship Granting authorship to senior individuals as courtesy or to add prestige to the paper. [19,22,23,24,25,26,27,31] Hostage authorship Including an undeserving individual as author because of unavoidable pressure.…”
Section: Survey Medical 2014mentioning
confidence: 99%
See 2 more Smart Citations